Guidelines for Conducting Action Research Studies in Software Engineering - Miroslaw Staron (e-Informatica Software Engineering Journal)
Context: Action research is popular in software engineering due to its industrial nature and promises of effective technology transfers. Yet, the methodology is still gaining popularity, and guidelines for conducting quality action research studies are needed. Objective: This paper aims to collect, summarize, and discuss guidelines for conducting action research in academia-industry collaborations. The guidelines are designed for researchers and practitioners alike. Method: I use existing guidelines for empirical studies and my own experiences to define guidelines for researchers and host organizations for conducting action research. Results: I identified 22 guidelines for conducting action research studies. They provide actionable recommendations on identifying the relevant context, planning and executing interventions (actions), reporting them, and reasoning around the ethics of action research. Conclusions: The paper concludes that the best way of engaging with action research is when we can be embedded in the host organization and when the collaboration leads to tangible change in the host organization and the generation of new scientific results.